“CONTINENTAL RIFTING, ACCOMPANYING PROCESSES” SYMPOSIUM DEDICATED TO THE MEMORY OF N.A. LOGACHEV AND E.E. MILANOVSKY, ‘ACADEMICIANS OF RIFTING’, 20–23 AUGUST 2013, IRKUTSK, RUSSIA - S. V. Rasskazov; S. P. Primina; T. A. Yasnygina; T. Yu. Tveritinova (Геодинамика и тектонофизика, 2015)
The article provides information about “Continental rifting, accompanying processes” Symposium dedicated to the memory of N.A. Logachev and E.E. Milanovsky, ‘Academicians of Rifting’. The symposium took place on 20–23 August 2013. It was initiated and arranged by the Institute of the Earth's Crust SB RAS and the Geological Faculty of the Irkutsk State University (Irkutsk) with participation of the Geological Faculty of Moscow State University. Topics of the symposium are reviewed.